2016
DOI: 10.1111/bjso.12151
|View full text |Cite
|
Sign up to set email alerts
|

Somewhere I belong: Long‐term increases in adolescents’ resilience are predicted by perceived belonging to the in‐group

Abstract: This study sought to examine the role of belonging in the increases in resilience observed following an adventure education programme (AEP). First, we demonstrate that group belonging makes a significant contribution to the improvement in resilience participants' experienced over the course of the AEP. Second, we demonstrate that this increase in resilience is maintained 9 months following the AEP and that group belonging maintained a significant contribution when controlling for participants' initial resilien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 69 publications
2
40
0
Order By: Relevance
“…Our findings for psychological resilience are consistent with a growing body of work demonstrating that, rather than being a property of the individual and static in nature, psychological resilience is built on a foundation of collective/social identity (Ungar 2005;Scarf, Moradi et al 2016;Scarf, Hayhurst et al 2017). With respect to the marked increases in resilience displayed by Māori youth, our findings are consistent with recent work involving Aboriginal youth in Canada (Ritchie, Wabano, Russell, et al 2014;Ritchie, Wabano, Corbiere, et al 2015).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings for psychological resilience are consistent with a growing body of work demonstrating that, rather than being a property of the individual and static in nature, psychological resilience is built on a foundation of collective/social identity (Ungar 2005;Scarf, Moradi et al 2016;Scarf, Hayhurst et al 2017). With respect to the marked increases in resilience displayed by Māori youth, our findings are consistent with recent work involving Aboriginal youth in Canada (Ritchie, Wabano, Russell, et al 2014;Ritchie, Wabano, Corbiere, et al 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Previously, we have demonstrated that the increases in self-esteem and resilience observed following a voyage on the Spirit of New Zealand are maintained several months after the voyage (Hunter et al 2013;Kafka et al 2016;Scarf, Moradi, et al, 2016;Scarf, Kafka, et al, 2018). With respect to the Tucker, a long-term follow-up is challenging due to the fact youth require considerable support to complete the Time 1 and Time 2 questionnaires.…”
Section: Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Adolescence marks the onset of a lifelong endeavor aimed at identity construction and social belonging, wherein youth begin to grapple with existential questions, such as “who am I?”, and “how do I fit in?” (Oyserman, 2001). Each of these dimensions—identity and belonging—is crucial to emotional wellbeing, although studies have focused predominantly on issues related to the effects of identity on self-definition (Scarf et al, 2016). Research has had less success investigating the ways in which belonging contributes to mental health.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for disabled individuals who maybe largely house bound, Minecraft may provide a way to interact with fellow group members frequently; helping to keep groups together that may only meet occasionally in person. It will also be important for future studies to investigate whether Minecraft can imbue groups with the sense of belonging and acceptance that are critical to their benefits ( Scarf et al , 2016a; Scarf et al , 2016b). …”
mentioning
confidence: 99%